БЎЛАЖАК ЖИСМОНИЙ ТАРБИЯ ЎҚИТУВЧИЛАРИНИНГ КАСБИЙ КОМПЕТЕНЦИЯЛАРИНИ ТАКОМИЛЛАШТИРИШНИНГ ПЕДАГОГИК ЗАРУРАТИ - Халмуратов, М.Т. (SCIENCE and SOCIETY, 2022)
The main goal of this article is to provide the fact that improving the professional competence of future physical education teachers.
Keywords: physical education; pedagogical problems; competitiveness; professional competence